Demographic distribution of odontogenic cysts in Isfahan (Iran) over a 23-year period (1988-2010) - Negin Khosravi; Sayed Mohammad Razavi; Mahsa Kowkabi; Amir Arsalan Navabi (Wolters Kluwer Medknow Publications, 2013)
Background: Odontogenic cysts are relatively common lesions which can cause different complications. As demographic information is lacking in Iran and specially in Isfahan, the aim of this study was to determine the prevalence of odontogenic cysts according to age, gender and affected area among patients referring to the Oral Pathology Department of the Dental School of Isfahan University of Medical Sciences (Iran) over a 23-year period. Materials and Methods: A total of 7412 diagnosed lesions recorded in the Oral Pathology Department archives of Isfahan Dental School between 1988 and 2010 were reevaluated, then odontogenic cysts were separated through reviewing microscopic slides according to the 2005 World Health Organization classification and variables such as age, gender, the infected jaw, and its specific region were obtained by SPSS Version 16.0 from the recorded database. Results: 21.62% of the lesions were odontogenic cysts, of which 48.72% were inflammatory and 51.28% were developmental cysts. These cysts were more common in the mandible. The mean age of patients was 29.53 ± 16.1. Male to female ratio was 1.31:1. The four most frequent odontogenic cysts were radicular cysts (35.12%), dentigerous cysts (25.77%), odontogenic keratocysts (22.58%) and residual cysts (12.98%). Conclusion: Odontogenic cysts are fairly frequent jaw lesions (21.62%), of which radicular cyst was the most common cyst. The four most common lesions constituted a sum of 96.45% of the total. In general, the prevalence rates in our study are similar to the studies from other geographic parts of the world but with a lower incidence of inflammatory cysts, higher prevalence of dentigerous cysts and residual cysts and also mandibular predominance for residual cysts.